PEMETAAN KEANEKARAGAMAN KACANG KORO (Phaseolus lunatus.L) di JAWA TIMUR BERDASAR METODE MORFOMETRIK SEBAGAI UPAYA KONSERVASI KEANEKARAGAMAN HAYATI - Elly Purwanti (Proceeding Biology Education Conference: Biology, Science, Enviromental, and Learning, 2014)
Abstract- This study has the scope Mapping diversity Phaseolus lunatus,L., in East Java based morphometric methods and conservation strategies . Thus limitations include : 1 ) Identification and mapping diversity Phaseolus lunatus , L based on morphometric method 2 ) management strategies of Phaseolus . The results of the survey in these areas in East Java , the existence ofPhaseolus lunatus L obtained several type . as follows : Trenggalek found 4 tipes , in Ponorogo 3 types , Jombang 3 types , Malang 2 types , Probolinggo 4types  , Madura 6 types . As a whole found 16 different types of seeds . Based on  morphological characters identified guide " Descriptor for Legume , The International Plant Genetic Resources , 2004 " . Phaseolus lunatus L, from 16 types obtained , again classified by 3 types grain size . Type of large grains with a diameter of ± 12 cm , called the Inca type , medium type with a diameter of ± 8cm called type Potato , small grains with a diameter of ± 5cm called type Sieva . Keywords :inventory, Arecaceae, waterfall, Irenggolo